Technology by fine particles classification of no metalic minerals. - Flores Chávez, Silvana (2009)
This article describes a general vision about the use of the Cyclosizer used mainly for the realization o experimental tests of metallic and non metallic minerals in the processing of minerals such as: gold bearing minerals and dolomite minerals, respectively. The cyclosizer is an elutriator that separates a specimen in specifically sized fractions using a technique that depends on the forces produced by the relative speed of the particles and the elutriation fluid. It is different from a conventional elutriation where the elutriation action takes place in a hydraulic cyclone where the fluid is spinning and the centrifuge forces are acting on the particles due to the gravity. The fluid models in the cyclone are stable and the changes in the condition of the atmosphere are not as critical as in the case of the conventional processing for elutriation. Also, the high cutting forces that are developed in the cyclone exceed any natural tendency in order to floccule the fine material and assure an excellent disposition of the particles.